FemaleSafe2Go / Mohd Haziq Hafizul … [et al.] - Hafizul, Mohd Haziq; Azhar, Shari Aisah; Haguan, Sofi Sohana; Bidder, Christy (Faculty of Computer and Mathematical Sciences, 2022)
Traveling is a good thing which will have a great impact on tourism industries, it is still worrisome for travelers especially female travelers due to the increasing rate of crime. Based on previous research, they stated that tourists in general are victims of crime as a result of their carelessness, lack of local knowledge, self-indulgence, and unfamiliarity with the area. Women, on the other hand, are arguably easier targets since they stand out more when they are alone. It is quite frustrating for people, especially women, to travel while facing the risk of being exposed to dangers. Thus, the idea of wanting to create a tracking application that can give a safer experience for female travelers called FemaleSafe2Go. This application is a user-friendly application with tons of security features. The main purpose of this application is to ensure the safety of female travelers, especially solo travelers while potentially decreasing their rate of exposure to violence. Our compact and easy-to-use applications are specialized on safety-based services such as tracker for tracking purposes, “Save Our Souls” system (SOS) for emergency purposes, and a gyroscopic enhanced module to detect whether the user is in danger through the orientation of the user’s respective device. To differentiate between this application and other safety-based applications such as BSafe and OneScream is that those applications tend to breach the user’ agreements for advertisement purposes. FemaleSafe2Go keeps all the users' data private and confidential since we prioritize safety of the users instead of monetization purposes.